Corrosion inhibition studies of cashew nut (Anacardium occidentale) on carbon steel in 1.0 M hydrochloric acid environment - Mohammed, Hassan; Sobri, Shafreeza (Elsevier, 2018)
The corrosion inhibitive characteristics of the cashew nut (Anacardium occidentale) were studied as an eco-friendly green corrosion inhibitor at ambient temperature of 25 °C using weight loss analysis and adsorption isotherms. The effect of inhibitor concentration (4–12 g/l) at immersion time of 3–12 days was evaluated. The inhibitive ability of cashew nut shows a significant inhibition efficiency of 86% at 12 g/l concentration for 3-days and 72.9% at 12-days, which are undoubtedly as a result of the absorption of the inhibitor molecules on the metal surface which serve as a barrier against corrosion of carbon steel in acidic medium. The adsorption mechanism was found to fit Tempkin isotherms. The average optimum free energy of absorption was calculated to be −17.374 kJ mol–1 indicating that the process was exothermic and physisorption.